К характеристике зараженности пресноводных брюхоногих моллюсков личиночными формами трематод - Стадниченко, А.П. (Вестник зоологии, 1974)
Gastropoda from the western regions of the Ukrainian SSR and the Lower Volga area were studied in the ecological and parasitological aspects. About 25 thousand molluscs of 46 species were investigated. In 31 species of molluscs 105 species of trematode larvae were found. The invasion extensiveness is shown as dependent on the season and sex of the host.